2013
DOI: 10.1557/mrc.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Hairy nanoparticle assemblies as one-component functional polymer nanocomposites: opportunities and challenges

Abstract: Over the past three decades, the combination of inorganic-nanoparticles and organic-polymers has led to a wide variety of advanced materials, including polymer nanocomposites (PNCs). Recently, synthetic innovations for attaching polymers to nanoparticles to create "hairy nanoparticles" (HNPs) has expanded opportunities in this field. In addition to nanoparticle compatibilization for traditional particle-matrix blending, neat-HNPs afford one-component hybrids, both in composition and properties, which avoids is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
217
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(223 citation statements)
references
References 152 publications
3
217
0
Order By: Relevance
“…[11][12][13][14] Recent advances in surface initiated ATRP and Cu-catalyzed "click" chemistry have led to an increasingly diverse group of polymer grafted, hairy nanoparticles (HNPs) that feature high ε r and refractive index core plus a polymer corona with tunable structure. [15][16][17] Solution cast films of these HNPs without an accompanying polymer matrix have recently been characterized for dielectric performance. Tchoul et al reported that hairy PS@TiO 2 matrix free assemblies at 27% v/v inorganic loading have a relative dielectric constant of 6.4, compared to 2.4 for neat PS, while maintaining low dielectric loss similar to PS (tan δ = 0.04 at 1 kHz).…”
Section: Original Research Papermentioning
confidence: 99%
“…[11][12][13][14] Recent advances in surface initiated ATRP and Cu-catalyzed "click" chemistry have led to an increasingly diverse group of polymer grafted, hairy nanoparticles (HNPs) that feature high ε r and refractive index core plus a polymer corona with tunable structure. [15][16][17] Solution cast films of these HNPs without an accompanying polymer matrix have recently been characterized for dielectric performance. Tchoul et al reported that hairy PS@TiO 2 matrix free assemblies at 27% v/v inorganic loading have a relative dielectric constant of 6.4, compared to 2.4 for neat PS, while maintaining low dielectric loss similar to PS (tan δ = 0.04 at 1 kHz).…”
Section: Original Research Papermentioning
confidence: 99%
“…The properties of particle brush materials (as well as other composite materials) can be finely tuned by controlling the grafting density at the organic/inorganic interface (Fernandes et al 2013). One effective strategy to control the initiator density is by intermixing the initiator with a nonreactive "dummy" coupling agent as illustrated in Fig.…”
Section: Initiationmentioning
confidence: 99%
“…These conformational transitions are particularly relevant in particle brushes in which the particle core radius equals the dimension of tethered chains and have been shown to influence the structure formation, interaction, as well as dynamic properties of particle brush materials (Choi et al 2010(Choi et al , 2012. The sensitive dependence of the physicochemical properties on the architecture of particle brush materials has fueled research into synthetic methodologies to control the architecture of grafted polymer chains and the implications of polymer-graft modification on the material properties and processability of particle brush materials (Fernandes et al 2013;Hui et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] These characteristics have demonstrated to be very strongly dependent on the dispersion state of the nanoparticles in the polymer matrix. 14,15 Nowadays it is well established that the dispersion state of nanoparticles, within a polymer matrix, controls the physical and mechanical properties of the nanocomposite. 16 Thus, beneficial effects on mechanical and physical properties would be improved when stable dispersion of nanoparticles (NPs) is achieved without formation of the aggregates.…”
Section: Introductionmentioning
confidence: 99%